Determinants of collaboration and innovation in creative industries a case of the Czech Republic - Stejskal, Jan; Hájek, Petr (2016)
The process of knowledge acquisition, creation and effective utilization is considered a key determinant of innovation activity.Thus, this process becomes a strong source of competitiveness.Knowledge is best transferred in a collaborative environment with strong links between actors. Here we focus on creative industries which can be characterized by a high importance of individuals and their social networks in the local and regional development. The paper deals with the determinants of cooperation and innovation in the creative industries, including knowledge acquisition from various sources, R&D activity and support, and creative individuals. We empirically show that firms from creative industries create innovation mainly through knowledge acquisition from clients and competition. The industry effect was also a significant determinant of innovation activity.